Practical approaches of issuers to ipo-implementation on the Czech capital market - Meluzín, Tomáš (Univerzita Pardubice, 2011)
Funding of the company development through the „Initial Public Offering“ has a large representation in the world and on the developed capital markets it has been one of the traditional ways for raising funds needed for business development. In Anglo-Saxon countries and Western Europe is the method of financing through IPO used by businesses for several decades already. Initial public offering on these markets began in large numbers from the beginning of the sixties of last century. Since then, the importance of IPO in the world scale is increasing and in recent years there are appearing the public offerings of shares even in the countries of Central and Eastern Europe. Also on the Czech capital market can be identified seven companies that joined this form of financing in the years 2004-2010. This article aims to identify the main characteristics of initial public offerings of shares which took place on the Czech capital market in its modern history, and to identify attitudes, opinions and experiences of each practising company.
Keywords: IPO; initial public offering; Czech capital market; practical approaches